Measurement of inclusive D*± production in two-photon collisions at LEP - Dova, María Teresa (1999)
Inclusive production of D*± mesons in two-photon collisions was measured by the L3 experiment at LEP. The data were collected at a centre-of-mass energy s s189 GeV with an integrated luminosity of 176.4 pb-1 . Differential cross sections of the process e+e-→e+e-D*±X are determined as functions of the transverse momentum and pseudorapidity of the D*± mesons in the kinematic region <mtext>1</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext><mtext><p</mtext>T<mtext>D</mtext>∗<mtext><5</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext> and <mtext>|η</mtext><mtext>D</mtext>∗<mtext>|</mtext><mtext><1.4</mtext>. The cross section integrated over this phase space domain is measured to be 132 ± 22 (stat.) ± 26 (syst.) pb. The differential cross sections are compared with next-to-leading order perturbative QCD calculations.